A perspective on the current treatment strategies for locally advanced rectal cancer. (August 2015) - Avallone, Antonio; Aloj, Luigi; Aprile, Giuseppe; Rosati, Gerardo; Budillon, Alfredo
Abstract: The introduction of total mesorectal excision (TME) and preoperative multimodality treatment have substantially improved the management of rectal cancer reducing local recurrence and increasing sphincter-saving surgery; distant metastases however remain a clinical challenge. Besides, although surgery remains the mainstay for cure of rectal cancer with the multimodality approach (chemotherapy, radiotherapy and surgery) being the standard of care for the majority of rectal cancer patients, there is a need of individualized risk-adapted treatment schemes based on clinico-pathological features because of treatment-induced morbidity and quality of life deterioration. This short viewpoint describes the emerging strategies addressing all these issues.